Space sustainability as a national priority in the United States. Issue 4 (December 2022) - Shields, Robert
Abstract: The U.S. government has a national security and economic security responsibility to address the challenge of space congestion. However, the U.S. government's fcurrent space sustainability efforts are insufficient to address growing congestion in orbital space caused by the proliferation of satellites in low-earth orbit (LEO). The U.S. government must raise national awareness of this challenge and drive a new sense of urgency for space sustainability. It must also establish and adequately fund a space traffic management (STM) regime at the Commerce Department. Furthermore, U.S. government agencies must employ more creative ways to promote commercial innovation in space sustainability services such as space situational awareness (SSA) and orbital debris mitigation. Strong public-private collaboration should underpin all efforts to promote space sustainability.